2020
DOI: 10.1002/ps.6056
|View full text |Cite
|
Sign up to set email alerts
|

Construction of oxime ester derivatives of osthole from Cnidium monnieri, and evaluation of their agricultural activities and control efficiency

Abstract: BACKGROUND: In order to discover natural-product-based pesticidal candidates, a series of coumarin-like derivatives containing oxime ester fragments at the C-8 position were prepared by structural modification of osthole, a natural plant product isolated from Cnidium monnieri. Their pesticidal activities were evaluated against two typically fruit trees/crop-threatening agricultural pests, Mythimna separata Walker and Tetranychus cinnabarinus Boisduval. RESULTS: Osthole was regioselectively oxidized by selenium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…(Table 11). Additionally, Ren et al reported a series of osthole derivatives containing oxime ester fragments at the C-8 position and their pesticidal activities [131]. Aldehyde intermediate 34 was synthesized as above, which was reacted with hydroxylamine hydrochloride in the presence of sodium hydroxide to give the oxime intermediate 45.…”
Section: Analogs Modified With An 8-substituent Of Coumarinmentioning
confidence: 99%
“…(Table 11). Additionally, Ren et al reported a series of osthole derivatives containing oxime ester fragments at the C-8 position and their pesticidal activities [131]. Aldehyde intermediate 34 was synthesized as above, which was reacted with hydroxylamine hydrochloride in the presence of sodium hydroxide to give the oxime intermediate 45.…”
Section: Analogs Modified With An 8-substituent Of Coumarinmentioning
confidence: 99%
“…Previously, we prepared a series of matrine esters , ( I and II , Figure ), andrographolide esters ( III , Figure ), and fraxinellone esters ( IV , Figure ) as pesticidal agents and found that some derivatives exhibited more potent pesticidal activities than their precursors and toosendanin (a botanical insecticide registered in China). More recently, we have prepared a series of osthole oxime esters ( V , Figure ) by structural modification of 3′-methy-l-2′-butylenyl at the C-8 position of osthole and found one derivative, (2′ E ,4′ E )-( p -chlorophenylcarbonyl)­oximinylosthole, that showed pronounced pesticidal activities against Tetranychus cinnabarinus Boisduval and Mythimna separata Walker . Based on the above results, to discover new high-value-added potential pesticidal agents from natural plant bioactive products, in this study, we want to investigate the importance of the lactone ring of osthole for pesticidal activities, and a series of novel target compounds (osthole-type ester derivatives, Figure ) were constructed by opening the lactone ring.…”
Section: Introductionmentioning
confidence: 96%
“…More recently, we have prepared a series of osthole oxime esters (V, Figure 1) by structural modification of 3′-methy-l-2′-butylenyl at the C-8 position of osthole and found one derivative, (2′E,4′E)-(pchlorophenylcarbonyl)oximinylosthole, that showed pronounced pesticidal activities against Tetranychus cinnabarinus Boisduval and Mythimna separata Walker. 11 Based on the above results, to discover new high-value-added potential pesticidal agents from natural plant bioactive products, in this study, we want to investigate the importance of the lactone ring of osthole for pesticidal activities, and a series of novel target compounds (osthole-type ester derivatives, Figure 1) were constructed by opening the lactone ring.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osthole (7-methoxy-8-isopentenoxycoumarin, C 15 H 16 O 3 ) is a natural coumarin-like compound most frequently isolated from the traditional Chinese medicine Cnidium monnieri (L.), and has obvious significant medical activities such as anti-inflammation, antiosteoporosis, anti-Alzheimer, antitumor, and so forth. Meanwhile, as osthole is less risky for human health and environment, it has been applied as antifungal, larvicidal, and anthelminthic agents against plant pathogens and insect pests in China for a long time. So far, osthole has been authorized to control powdery mildews, gray moulds, injurious mites, aphids, and thrips in China, and it seems to be a perfect botanical pesticide for controlling plant pests and diseases simultaneously. However, most botanical pesticides have limitations of slow action and short persistence for pest and disease management. , The pesticidal activities of osthole are far from being comparable to traditional agrochemicals, and its utilization efficiency should be further improved to meet the actual demands.…”
Section: Introductionmentioning
confidence: 99%